Modern European criticism and theory : a critical guide - Wolfreys, Julian, 1958- (Edinburgh University Press, 2006)
Providing an overview of literary theory in Europe, this guide presents the ideas within European 'theory', focusing on the thought of major voices in poetics, philosophy, linguistics, and psychoanalysis, as well as in literary and cultural studies. The essays examine how conceptions of subjectivity, identity, and gender have been questioned.